1998
DOI: 10.1063/1.121863
|View full text |Cite
|
Sign up to set email alerts
|

Quasiphase matched second harmonic generation in ZnSe waveguide structures modulated by focused ion beam implantation

Abstract: Second harmonic generation is investigated in a ZnSe/ZnS0.22Se0.78 waveguide grown by metal organic vapor phase epitaxy on (001) GaAs substrate. Phase matching is achieved by a first order periodic modulation of the nonlinear susceptibility χ(2) within the waveguide structure. The modulation is generated by a focused ion beam implantation technique, resulting in a well confined damage of the crystalline structure. The observed phase matching wavelengths corresponding to various modulation periods between 1.6 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Epitaxial ZnSe thin films are usually grown on GaAs substrates to achieve lattice matching (0.27% mismatch) for applications in laser diodes [2], solar cells [3], second harmonic generation [10] and nonlinear switching [11]. However, the deposition of non-epitaxial several microns thick films of ZnSe on silicon (Si) is challenging mainly because of dissimilar thermal expansion and distinct chemical properties [12].…”
Section: Introductionmentioning
confidence: 99%
“…Epitaxial ZnSe thin films are usually grown on GaAs substrates to achieve lattice matching (0.27% mismatch) for applications in laser diodes [2], solar cells [3], second harmonic generation [10] and nonlinear switching [11]. However, the deposition of non-epitaxial several microns thick films of ZnSe on silicon (Si) is challenging mainly because of dissimilar thermal expansion and distinct chemical properties [12].…”
Section: Introductionmentioning
confidence: 99%
“…Only few investigations report on the dispersion of ͉ 14 (2) ͉ in wide-gap II-VI semiconductors, 13,14 although these materials possess high SHG coefficients and thus have the potential for efficient SHG in the visible spectral region using II-VI waveguide structures. [15][16][17] A microscopic expression for ͉ 14 (2) ͉ can be obtained from second-order perturbation calculations. [18][19][20][21][22] However, a complete understanding of the dispersion of ͉ 14 (2) ͉ requires detailed information of the energies and wave functions of the electronic states in the entire first Brillouin zone ͑BZ͒.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, promising results have also shown that a multi-layer strategy 6 and artificial periodic structures 14 can be employed to improve phase matching.…”
Section: Cw Blue-green Light Emission From Gan and Sic By Sum-frequenmentioning
confidence: 98%